2020
DOI: 10.1177/0309324719892732
|View full text |Cite
|
Sign up to set email alerts
|

Determination of constitutive relation from miniature tensile test with digital image correlation

Abstract: The determination of constitutive relation from the miniature tensile test is of high interest in multiple areas. Here, a convenient experimental method is proposed to determine the true stress–strain curve from the miniature tensile test. The instantaneous cross-sectional area is estimated by only one camera in aid of digital image correlation technique. This method was applied on commercial pure titanium and aluminum 6061 alloys, and the results indicate that the extracted true stress–strain curves are not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Compared with traditional measurement methods, DIC is a non-destructive testing, and it can realize real-time measurement and have high calculation accuracy. 2124 Therefore, DIC has been used by some scholars to study the fracture characteristics of cementious materials gradually. Corr et al 22 found that the distributed softening at the carbon fiber–reinforced plastic (CFRP)–substrate interface occurs ahead of macrocrack formation by DIC technique.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional measurement methods, DIC is a non-destructive testing, and it can realize real-time measurement and have high calculation accuracy. 2124 Therefore, DIC has been used by some scholars to study the fracture characteristics of cementious materials gradually. Corr et al 22 found that the distributed softening at the carbon fiber–reinforced plastic (CFRP)–substrate interface occurs ahead of macrocrack formation by DIC technique.…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude of vertical strain at the crack tip and its effect on the area around the crack are two factors used to explain the crack propagation tendency [4,[35][36][37]. These two factors can be implemented utilizing the full-field displacement distribution acquired from the DIC technique [13,38]. The pre-cut crack length of 3 mm on the samples and ROI values of 5 × 5 mm 2 near the crack tip were compared.…”
Section: Investigation Of Strain Distributionmentioning
confidence: 99%
“…The use of full-field optical techniques to measure materials' displacement and surface deformation has recently increased significantly. Digital image correlation (DIC) is a measurement technique widely used in experimental mechanics because its advantages include non-contact, fullarea optical measurement, high sensitivity, no special environmental requirements, and easy handling [12][13][14][15]. In this method, the deformation carrier is the tracking speckle patterns sprayed on the material surface or the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the r p measurement was achieved by DIC, which has already been successfully utilized in strain measurements. [51][52][53][54]…”
Section: Theoretical Analysismentioning
confidence: 99%